Leptin and resistin in overweight patients with and without asthma - Muc, Magdalena (2014)
Background: Excess body mass increases the risk of development of asthmatic symptoms and their severity and decreases the treatment effectiveness. One of the hypotheses explaining the link between the two diseases concerns the adipokines, hormones produced by adipose tissue with a proinflammatory character. The aim of this study was to compare the levels of the adipokines (leptin and resistin) between overweight asthmatic patients, asthmatic patients with normal weight and overweight patients without asthma. Methods: 80 peripheral blood samples were collected from patients and blood serum extracted. Three groups were selected: overweight asthmatic patients (BMI ≥ 25), overweight patients without asthma and asthmatic patients with normal weight (BMI < 25). Waist circumference of the patients was measured (cut-off points were 80 cm for women and over 94 cm for men) and a skin prick test performed. Comparison of adipokine concentration between the 3 groups was made and association between these concentrations and the measurements was performed. Results: Although the concentrations of both adipokines were slightly higher for overweight asthmatic patients compared to overweight healthy p atients, these differences were not significant. A significant association was found between leptin concentration and both BMI (p < 0.01) and waist circumference (p < 0.01). A difference for this cytokine was also found between asthmatic and non-asthmatic female patients (p < 0.05). Conclusions: As expected overweight patients with BMI ≥ 25 and patients with increased waist circumference showed higher leptin levels. We suggest that the studied cytokines, with a stronger indication for leptin, can elicit asthmatic inflammation in obese phenotype of asthma that affects more frequently women.